Competitive intelligence practices and organizational performance linkage: a review / Dian Aszyanti Atirah Mohd Asri and Ainul Mohsein Binti Abdul Mohsin - Mohd Asri, Dian Aszyanti Atirah; Abdul Mohsin, Ainul Mohsein (Universiti Teknologi MARA, Perlis, 2020)
Scholars have intensely researched Competitive Intelligence or CI for decades. This topic has been under constant investigation and development concerning business strategy in soaring business performance. This paper critically examines and integrates the Competitive Intelligence Practices by different industries and its relationship on organizational performances. The review employed Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and utilizes three databases (Science Direct, Scopus, and Proquest) from January 2014 to November 2019. This timeframe and databases were preferred because the articles collected have been through a quality control process and comprehensive source for research performance data and analytics. As many as 666 articles were narrowed down to 20 articles to meet the criteria of this study. Conclusively, six main themes were identified, which are Organizational awareness, CI process, Social capital, CI Challenges, Competitive advantages and Sustainability based on the thematic analyses. Furthermore, another five sub-themes emerge from these key themes. A deduction is made concerning a relationship between Competitive Intelligence Practices and Organizational performance. This paper also suggests conducting more studies in service industries, especially the hospitality industry because of its economic impact and the changing landscape in today's consumer.